GUNUNGPATI SEBAGAI KAWASAN PENYANGGA KOTA SEMARANG - dkk., Moch. Samsul Arifin (Indonesian Journal of Conservation, 2013)
This paper describes study of development of Gunungpati as effect of city growth and its impact for burying capacity of District Gunungpati as buffer zone.ÃÂ Suitability of land in the District Gunungpati the category is suitable for residential land is an area of Ã¢â¬â¹Ã¢â¬â¹1612.2 Ha, 1079,3 Ha categories according amounted and 2719.5 areas unsuitable for residential use Gunungpati District. Areas which are not suitable for residential land has a high slope, degraded land, land for buffer zones and land for protected area. Growth and district development Gunungpati equitable development aimed at the area between the center and periphery are directed at areas that still have land suitability and environmental carrying capacity, thus retaining the agricultural and conservation areas in order to maintain the functioning of urban areas as buffer zones. Gunungpati districts in the future spatial planning is prioritized as a green area with vegetation - vegetation is able to reduce the criticality of land in District Gunungpati in particular, and can keep the Garang River discharge runoff in general so as to minimize flooding in the city of Semarang. .Keywords : buffer zones , Gunungpati , spatialÃÂ Tulisan ini bertujuan untuk mengkaji pembangunan di Gunungpati akibat pengembangan kota dan dampaknya terhadap daya dukung lahan di Kecamatan Gunungpati sebagai kawasan penyangga. Kesesuaian lahan di Kecamatan Gunungpati pada kategori sangat sesuai untuk lahan permukiman adalah seluas 1612,2 Ha, kategori sesuai sebesar 1079,3 Ha dan kawasan yang kurang sesuai 2719,5 digunakan untuk permukiman Kecamatan Gunungpati. Kawasan yang yang tidak sesuai untuk lahan pemukiman adalah lahan yang memiliki tingkat kemiringan tinggi, lahan kritis, lahan untuk kawasan penyangga dan lahan untuk kawasan lindung. Pembangunan dan pengembangan Kecamatan Gunungpati yang ditujukan untuk pemerataan pembangunan wilayah antara pusat dan pinggiran diarahkan pada daerah yang masih memiliki kesesuaian lahan dan daya dukung lingkungan, sehingga tetap mempertahankan kawasan pertanian dan konservasi dalam rangka mempertahankan fungsi wilayah sebagai wilayah penyangga perkotaan. Kecamatan Gunungpati dalam penataan ruang pada masa mendatang lebih diprioritaskan sebagai kawasan hijau dengan vegetasi-vegetasi yang mampu mereduksi kekritisan lahan di Kecamatan Gunungpati pada khususnya, dan dapat menjaga debit limpasan Sungai Garang pada umunya sehingga mampu meminimalisir banjir di Kota Semarang. Kata kunci: kawasan penangga, Gunungpati, tata ruang ÃÂ